Prediction of Tropical Cyclones’ Characteristic Factors on Hainan Island Using Data Mining Technology - Ruixu Zhou; Wensheng Gao; Bowen Zhang; Xianggan Fu; Qinzhu Chen; Song Huang; Yafeng Liang (Advances in Meteorology)
A new methodology combining data mining technology with statistical methods is proposed for the prediction of tropical cyclones’ characteristic factors which contain latitude, longitude, the lowest center pressure, and wind speed. In the proposed method, the best track datasets in the years 1949~2012 are used for prediction. Using the method, effective criterions are formed to judge whether tropical cyclones land on Hainan Island or not. The highest probability of accurate judgment can reach above 79%. With regard to TCs which are judged to land on Hainan Island, related prediction equations are established to effectively predict their characteristic factors. Results show that the average distance error is improved compared with the National Meteorological Centre of China.